A topology-aware method for scientific application deployment on cloud. (1st January 2014) - Fan, Pei; Chen, Zhenbang; Wang, Ji; Zheng, Zibin; Lyu, Michael R.
Nowadays, more and more scientific applications are moving to cloud computing. The optimal deployment of scientific applications is critical for providing good services to users. Scientific applications are usually topology-aware applications. Therefore, considering the topology of a scientific application during the development will benefit the performance of the application. However, it is challenging to automatically discover and make use of the communication pattern of a scientific application while deploying the application on cloud. To attack this challenge, in this paper, we propose a framework to discover the communication topology of a scientific application by pre-execution and multi-scale graph clustering, based on which the deployment can be optimised. In addition, we present a set of efficient collective operations for cloud based on the common interconnect topology. Comprehensive experiments are conducted by employing a well-known MPI benchmark and comparing the performance of our method with those of other methods. The experimental results show the effectiveness of our topologyaware deployment method.